Local nearrings, their structure, and the GAP system - Raievska, I.; Raievska, M.; Раєвська, Ірина; Раєвська, Марина (Institute of Mathematics, NAS of Ukraine, 2025)
UDC 512.6 We present an overview of the current state of research of finite local nearrings. In particular, it contains all recently obtained results on the classification of local nearrings.